Credit crunched: Single parents, universal credit and the struggle to make work pay - Mike Brewer; Paola De Agostini (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This paper examines the likely impact of Universal Credit on the incomes and work incentives of single parent families. Using the UK module of EUROMOD (version F6.20), we also simulate how single parents' household income, and their work incentives, would change following adjustments to the universal credit structure. We examine four main alternative scenarios: 1) reducing the overall universal credit taper rate from 65% to 55%; 2) Increasing the basic (standard) allowances in universal credit for single parents; 3) Increasing the earnings disregard in universal credit for single parents and 4) Increasing the income tax threshold for the basic tax rate. We also examine the impact on single parents of an increase in the minimum wage. Finally, we examine the impact on the Exchequer of a five percentage point increase in the single parent employment rate, in terms of benefits saved and taxes paid.
Keywords: C15; H24; I38; 330; microsimulation; income distribution; universal credit; single parents; work incentives